A case report on renal metastasis as an unusual presentation of choriocarcinoma - Meimei Huang; Yu Ma (BMC, 2024)
Abstract Background Choriocarcinoma is an aggressively invasive neoplasm, characterized by its rapid proliferation and propensity for metastasis to distant organs via hematogenous dissemination. Lungs (80%), vagina (30%), pelvis (20%), liver (10%), and brain (10%) are the most frequently metastasized organs. Renal metastases are very rare. The clinical manifestations of choriocarcinoma varies depending on the site of disease, making diagnosis challenging. In this report, we provide a clinical case of choriocarcinoma with metastases to the renal and pulmonary systems, displaying symptoms akin to those observed in ectopic pregnancy. Case presentation A 27-year-old female, G2P1, with a previous history of full-term pregnancy in 2018, presented to the hospital with the onset of vaginal bleeding and accompanying abdominal aches. Investigations uncovered a left adnexal mass with a human chorionic gonadotropin (hCG) level of 77,4 mIU/mL and a left pulmonary nodule measuring 31 mm x 21 mm. Laparoscopy was performed due to the high suspicion of an ectopic pregnancy. However, no visible villi were identified during the surgery, and postoperative blood hCG levels continued to rise. A diagnostic curettage also failed to reveal any villi, maintaining the suspicion of a persistent ectopic pregnancy. Following two ineffective courses of methotrexate therapy, the patient was referred to our facility. Prior to her referral, an ultrasound had indicated a mass in the right kidney. However, upon arrival at our hospital, subsequent ultrasonography failed to detect any renal masses. Despite two months of outpatient monitoring, there was a sudden and significant increase in her serum hCG levels. An emergency laparoscopy was performed, revealing no pregnancy-related lesion. After surgery, the patient's hCG levels dropped dramatically to less than one-tenth of the original amount. Multisite enhanced computed tomography(CT)revealed suspicious lesions in both the renal and pulmonary regions. Upon thorough multidisciplinary consultation, a diagnosis of choriocarcinoma was entertained. Consequently, the patient successfully underwent eight cycles of chemotherapy and has remained recurrence-free for the past year. Conclusions This case underscores the potential for choriocarcinoma in women of reproductive age who exhibit radiological signs of renal masses. Early and accurate diagnosis, followed by prompt intervention, is essential to prevent needless surgery procedures.